PUBLICATIONS RECEIVED (Academy of Management Review, 1995)
The article presents a list of books received by the periodical, including “Benchmarking Book,” by Michael J. Spendolini, “Benchmarking for Competitive Advantage,” by Robert J. Boxwell, Jr., and “Age of Paradox,” by Charles Handy.